Gentrification pathways and their health impacts on historically marginalized residents in Europe and North America: Global qualitative evidence from 14 cities. (November 2021) - Anguelovski, Isabelle; Cole, Helen V.S.; O'Neill, Ella; Baró, Francesc; Kotsila, Panagiota; Sekulova, Filka; Pérez del Pulgar, Carmen; Shokry, Galia; García-Lamarca, Melissa; Argüelles, Lucia; Connolly, James JT; Honey-Rosés, Jordi; et al.
Abstract: As global cities grapple with the increasing challenge of gentrification and displacement, research in public health and urban geography has presented growing evidence about the negative impacts of those unequal urban changes on the health of historically marginalized groups. Yet, to date comprehensive research about the variety of health impacts and their pathways beyond single case sites and through an international comparative approach of different gentrification drivers and manifestations remains scarce. In this paper, we analyze qualitative data on the pathways by which gentrification impacts the health of historically marginalized residents in 14 cities in Europe and North America. We build on 77 interviews with key neighborhood stakeholders. Data analysis indicates four main concurrent processes: Threats to housing and financial security; Socio-cultural displacement; Loss of services and amenities through institutional gentrification; and Increased risks of criminal behavior and compromised public safety. Gentrification is experienced as a chain of physical and emotional community and individual traumas – an overall shock for historically marginalized groups – because of permanent pressures of insecurity, loss, state of displaceability, and the associated exacerbation of socio-environmental disadvantages. Highlights: Multiple pathways account for the impacts of gentrification on health. Pathways to poor health include economic security and socio-cultural displacement. Marginalized residents also suffer from a loss of public services and amenities. Last, they face increased risks of criminal behavior and compromised public safety. Gentrification is thus experienced as a chain of community and individual traumas.